2005
DOI: 10.1111/j.1365-2796.2004.01436.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of QT interval duration with carotid intima media thickness in a clinically healthy population undergoing cardiovascular risk screening

Abstract: Objectives. To investigate the relationship between cardiac repolarization (QT interval duration) and intima media thickness (IMT) of the carotid arteries as surrogate measures of subclinical atherosclerosis. Design. Prospective study with consecutive subjects enrolled in the SAPHIR program (Salzburg Atherosclerosis Prevention Program in Subjects at High Individual Risk). Setting. The analysis of the material was performed at the departments of medicine and neurology of a university hospital. Subjects. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 32 publications
5
30
1
Order By: Relevance
“…As for the duration of QT duration in our study, the mean length of QTc interval was in accordance with values observed in other epidemiological studies that aim to investigate the association of QT interval with other predictors of vascular risk, such as carotid intima-media thickness [1] or insulin resistance indexes [2]. It is thus not surprising that the mean duration of QTc in our population was within the normal range, as we focused on a clinically healthy population.…”
supporting
confidence: 83%
“…As for the duration of QT duration in our study, the mean length of QTc interval was in accordance with values observed in other epidemiological studies that aim to investigate the association of QT interval with other predictors of vascular risk, such as carotid intima-media thickness [1] or insulin resistance indexes [2]. It is thus not surprising that the mean duration of QTc in our population was within the normal range, as we focused on a clinically healthy population.…”
supporting
confidence: 83%
“…23 QT interval has also been shown to be associated with subclinical arterial disease. [24][25][26] Thus, QT interval prolongation, as a marker of ventricular hypertrophy or subclinical arterial disease, may predict future CVD events.…”
Section: Discussionmentioning
confidence: 99%
“…Ours is the largest study to have investigated the association between subclinical arterial disease and QT interval prolongation, but there have been a few other cross-sectional studies addressing this question using other structural markers of subclinical arterial disease (10)(11)(12). The Insulin Resistance Atherosclerosis Study (IRAS) investigated the association between carotid intima media thickness and QTc in 912 nondiabetic subjects without coronary artery disease and found a close association between carotid atherosclerosis and QT interval prolongation (10).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several epidemiological studies have shown that QT interval prolongation predicts the risks of clinical arterial disease (5-9) as well as sudden cardiac death (5). Likewise, a few cross-sectional studies have suggested a positive association between QT interval prolongation and subclinical arterial disease, such as carotid intima media thickness (10)(11)(12). However, there is significant uncertainty about the association between QT interval prolongation and other forms of subclinical arterial disease.…”
Section: Introductionmentioning
confidence: 99%